Efficacy of Different Ibuprofen Formulations with Two Prescription Methods on Post Endodontic Pain of Teeth with Irreversible Pulpitis: A Randomized Clinical Trial - Zadsirjan, Saeede; Haeri, Ali; Mohammadi, Elham; Beiraghdar, Sanaz; Hosseini, Mohammadreza; Heidari , Soolmaz (Iranian Endodontic Journal, 2022)
Introduction: Pain management during root canal therapy and after that is of great importance in endodontics. This study aimed to compare the effect of two non-steroidal anti-inflammatory drugs (NSAIDs); ibuprofen and ibuprofen lysine with two methods of prescription on pain after single-visit root canal treatment of first and second mandibular molar teeth with irreversible pulpitis. Materials and Methods: This randomized study recruited subjects experiencing moderate to severe pain from a tooth diagnosed with symptomatic irreversible pulpitis (n = 120). Subjects were randomized to receive 400 mg ibuprofen acid or 400 mg ibuprofen lysine regularly or on demand. The primary objective was to measure changes in pain scores at post-operative time frames of 6, 12, 18, 24, 48 and 72 hours after the root canal treatment on a 0-10 numerical rating scale (NRS). Independent T-test, Non-parametric Kruskal-Wallis Test and Friedman Test were used to analyze the data. Results: Kruskal-Wallis analysis showed a significant difference in NRS score between on-demand ibuprofen group and regular ibuprofen group and also between regular ibuprofen lysine group and regular ibuprofen group at 6 hours after the treatment (P<0.05). But no remarkable difference was observed in the recorded mean pain intensity of four study groups in the other time frames (P>0.05). Conclusions: Based on this randomized clinical trial, there was no significant difference in the pain intensity of patients using ibuprofen and ibuprofen lysine. Additionally, there was no significant difference in the degree of pain between the on-demand and regular groups, despite the fact that patients in the on-demand group used less medications. Due to the multiple negative effects of NSAIDs, it would be wise to prescribe ibuprofen on demand.